Effect of faecal calprotectin assay variability on the management of inflammatory bowel disease and potential role of faecal S100A12. Issue 12 (22nd July 2017) - Whitehead, Simon John; Ford, Clare; Gama, Rousseau Mariano; Ali, Ala; McKaig, Brian; Waldron, Jenna Louise; Steed, Helen; Brookes, Matthew James
Abstract : Aims: To prospectively evaluate whether between-assay variability of different faecal calprotectin (f-Cp) assays influences diagnostic accuracy for inflammatory bowel disease (IBD) in a cohort of patients with confirmed IBD and irritable bowel syndrome (IBS). To also evaluate the diagnostic accuracy of faecal S100A12 (f-S100A12) against f-Cp in the same patient cohort and assess whether f-S100A12 offers additional diagnostic value. Methods: F-Cp using four commercially available f-Cp assays, f-S100A12 and blood biomarkers were measured in patients, recruited from the local IBD clinic, who had established IBS or active ulcerative colitis (UC) and Crohn's disease (CD). Diagnostic sensitivities and specificities for each assay and biomarker were calculated and compared. Results: Median f-Cp levels in all assays were significantly higher in UC (347–884 µg/g; n=28) and CD (377–838 µg/g; n=15) compared with IBS (6–27 µg/g; n=17). Sensitivities and specificities at 50 µg/g were 94%–100% and 82%–100%,  respectively. Median f-S100A12 levels were significantly higher in UC (81.0 µg/g; IQR 38.3–159.8) and CD (47.2 µg/g; IQR 5.3–108.9) compared with IBS (0.7 µg/g; IQR 0.5–0.8). At 2.8 µg/g, f-S100A12 had a sensitivity of 97% and specificity of 94%. The blood biomarkers demonstrated sensitivities and specificities of 44%–63% and 80%–92%,  respectively. Conclusions: The diagnostic sensitivity of the calprotectin assays was similar despite inter-kit variability in absolute values. There is a need for f-Cp assay standardisation, but in its absence assay-specific cut-off values may optimise their diagnostic performance. F-S100A12 demonstrated comparable sensitivity and specificity to f-Cp and although a research tool at present, may have a future role to play in the diagnosis and management of these patients.